Penerapan Model Problem based learning pada Mata Pelajaran Ekonomi untuk Meningkatkan Pemahaman Konsep Peserta Didik MA Hidayatullah Jembrana - Ishak, Maulana; Sujana, I Nyoman (Universitas Pendidikan Ganesha, 2024)
The kind of this exploration was study hall activity exploration (vehicle) in two cycles. The subjects of this review were 21 understudies of class X IPS MA Hidayatullah Jembrana. The object of this examination was the comprehension of understudies' ideas in the field of monetary learning through the use of issue-based learning. The instruments used to gather the information in this review were the type of perception sheets on the execution of financial learning, composed tests, and documentation. The information investigation procedure utilized is illustrative and quantitative examination. The consequences of the review demonstrated that learning financial matters with an issue-based learning approach can work on how understudies might interpret ideas in financial aspects of learning. For this situation, the typical upsides of class X sociologies understudies have expanded in pre-activity trials of 65 to the primary pattern of 73, the second pattern of 82, and the expansion in normal rate worth of every sign of idea grasping in the principal pattern of 70% expanded by 80% in the second cycle with high models.